Predictors for long‐term survival after transcatheter edge‐to‐edge mitral valve repair. (28th March 2017) - Orban, Mathias; Orban, Martin; Lesevic, Hasema; Braun, Daniel; Deseive, Simon; Sonne, Carolin; Hutterer, Lisa; Grebmer, Christian; Khandoga, Alexander; Pache, Jürgen; Mehilli, Julinda; Schunkert, Heribert; et al.
Abstract : Objectives: To determine predictors for long‐term outcome in high‐risk patients undergoing transcatheter edge‐to‐edge mitral valve repair (TMVR) for severe mitral regurgitation (MR). Background: There is no data on predictors of long‐term outcome in high‐risk real‐world patients. Methods: From August 2009 to April 2011, 126 high‐risk patients deemed inoperable were treated with TMVR in two high‐volume university centers. Results: MR could be successfully reduced to grade ≤2 in 92.1% of patients (116/126 patients). Long‐term clinical follow‐up up to 5 years (95.2% follow‐up rate) revealed a mortality rate of 35.7% (45/126 patients). Repeat mitral valve treatment (surgery or intervention) was needed in 19 patients (15.1%). Long‐term clinical improvement was demonstrated with 69% of patients being in NYHA class ≤II. In a multivariable Cox regression analysis, the post‐procedural grade of MR (hazard ratio [HR] 1.55 per grade, P  = 0.035), the left ventricular ejection fraction (HR 0.58 for difference between 75th and 25th percentile, P  = 0.031) and the glomerular filtration rate (HR 0.33 for 75th vs 25th percentile, P  < 0.001) were independent predictors for long‐term mortality. Patients with primary MR and a post‐procedural MR grade ≤1 had the most favorable long‐term outcome. Conclusions: This study determines predictors of long‐term clinical outcome after TMVR and demonstrates that the grade of residual MR determines long‐term survival. Our data suggest that it might be of benefit reducing residual MR to the lowest possible MR grade using TMVR—especially in selected high‐risk patients with primary MR who are not considered as candidates for surgical MVR.